2022
DOI: 10.3390/biom12121743
|View full text |Cite
|
Sign up to set email alerts
|

How Can Dupilumab Cause Eosinophilic Pneumonia?

Abstract: Reports of eosinophilic pneumonia (EP) as a side effect of dupilumab administration are limited in previous studies. Herein, we report two cases in which EP developed subsequent to the administration of dupilumab for eosinophilic chronic rhinosinusitis (ECRS). Case 1: A 55-year-old woman presented with ECRS, eosinophilic otitis media, and bronchial asthma, and was treated with dupilumab for ECRS. Five weeks later, fever and dyspnea developed, and infiltration shadows were observed in her lungs. The peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Dupilumab‐induced hypereosinophilia is reported in 4%–14% of patients who are treated with dupilumab for CRSwNP, asthma, or atopic dermatitis 72 . Although hypereosinophilic syndrome emerging during dupilumab treatment is rare, it constitutes a clinical and diagnostic challenge and should not be disregarded 73–78 . Increased eosinophil levels generally arise and return back to normal within the first half year of dupilumab treatment 79,80 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dupilumab‐induced hypereosinophilia is reported in 4%–14% of patients who are treated with dupilumab for CRSwNP, asthma, or atopic dermatitis 72 . Although hypereosinophilic syndrome emerging during dupilumab treatment is rare, it constitutes a clinical and diagnostic challenge and should not be disregarded 73–78 . Increased eosinophil levels generally arise and return back to normal within the first half year of dupilumab treatment 79,80 .…”
Section: Discussionmentioning
confidence: 99%
“…72 Although hypereosinophilic syndrome emerging during dupilumab treatment is rare, it constitutes a clinical and diagnostic challenge and should not be disregarded. [73][74][75][76][77][78] Increased eosinophil levels generally arise and return back to normal within the first half year of dupilumab treatment. 79,80 dupilumab could be continued.…”
Section: 9mentioning
confidence: 99%
“…Dupilumab has only been used in one pediatric patient, who had a good response [24]. However, as we were selecting manuscripts and carrying out the detailed analysis, we found some case reports that have linked it as a cause of ICEP [28,29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…3 Kurihara et al reported two similar cases with high-grade eosinophilia and emphasized fever and dyspnea as initial symptoms of eosinophilic pneumonia. 4 Eger al. described four oral corticosteroid (OCS)-dependent asthma patients in whom IL-5 pathway biologics were switched to dupilumab leading to the development of eosinophilic pneumonia in one patient.…”
Section: Discussionmentioning
confidence: 99%
“…Nishiyama et al measured the serum cytokine levels in two cases of dupilumab‐associated eosinophilic pneumonia and found elevated IL‐5, but not in patients who did not develop dupilumab‐associated eosinophilic pneumonia 3 . Kurihara et al reported two similar cases with high‐grade eosinophilia and emphasized fever and dyspnea as initial symptoms of eosinophilic pneumonia 4 . Eger et al described four oral corticosteroid (OCS)‐dependent asthma patients in whom IL‐5 pathway biologics were switched to dupilumab leading to the development of eosinophilic pneumonia in one patient 5 .…”
Section: Discussionmentioning
confidence: 99%